Matrix metalloproteinase 9‐mediated shedding of syndecan 4 in response to tumor necrosis factor α: a contributor to endothelial cell glycocalyx dysfunction. Issue 11 (13th August 2014) - Ramnath, Raina; Foster, Rebecca R.; Qiu, Yan; Cope, George; Butler, Matthew J.; Salmon, Andrew H.; Mathieson, Peter W.; Coward, Richard J.; Welsh, Gavin I.; Satchell, Simon C.
Abstract : The endothelial surface glycocalyx is a hydrated mesh in which proteoglycans are prominent. It is damaged in diseases associated with elevated levels of tumor necrosis factor α (TNF‐α). We investigated the mechanism of TNF‐α‐induced disruption of the glomerular endothelial glycocalyx. We used conditionally immortalized human glomerular endothelial cells (GEnCs), quantitative PCR arrays, Western blotting, immunoprecipitation, immunofluorescence, and dot blots to examine the effects of TNF‐α. TNF‐α induced syndecan 4 (SDC4) mRNA up‐regulation by 2.5‐fold, whereas cell surface SDC4 and heparan sulfate (HS) were reduced by 36 and 30%, respectively, and SDC4 and sulfated glycosaminoglycan in the culture medium were increased by 52 and 65%, respectively, indicating TNF‐α‐induced shedding. Small interfering (siRNA) knockdown of SDC4 (by 52%) caused a corresponding loss of cell surface HS of similar magnitude (38%), and immunoprecipitation demonstrated that SDC4 and HS are shed as intact proteoglycan ectodomains. All of the effects of TNF‐α on SDC4 and HS were abrogated by the metalloproteinase (MMP) inhibitor batimastat. Also abrogated was the associated 37% increase in albumin passage across GEnC monolayers. Specific MMP9 knockdown by siRNA similarly blocked TNF‐α effects. SDC4 is the predominant HS proteoglycan in the GEnC glycocalyx. TNF‐α‐induced MMP9‐mediated shedding of SDC4 is likely to contribute to the endothelial glycocalyx disruption observed in diabetes and inflammatory states.—Ramnath, R., Foster, R. R., Qiu, Y., Cope, G., Butler, M. J., Salmon, A. H., Mathieson, P. W., Coward, R. J., Welsh, G. I., Satchell, S. C., Matrix metalloproteinase 9‐mediated shedding of syndecan 4 in response to tumor necrosis factor α: a contributor to endothelial cell glycocalyx dysfunction. FASEB J. 28, 4686–4699 (2014). www.fasebj.org